The Blanco DECam bulge survey I. The survey description and early results - Rich, R. Michael; Johnson, Christian I.; Young, Michael; Simion, Iulia T.; Clarkson, William I.; Pilachowski, Catherine; Michael, Scott; Kunder, Andrea; Vivas, A. Katherina; Koch-Hansen, Andreas; Marchetti, Tommaso; Ibata, Rodrigo; et al. (Monthly notices of the Royal Astronomical Society, 2020)
The Blanco Dark Energy Camera (DECam) Bulge survey is a Vera Rubin Observatory (LSST) pathfinder imaging survey, spanning ∼200 deg2 of the Southern Galactic bulge, −2° < b < −13° and −11° < l < +11°. We have employed the CTIO-4 m telescope and the DECam to image a contiguous ∼200 deg2 region of the relatively less reddened Southern Galactic bulge, in SDSS u + Pan-STARRSgrizy. Optical photometry with its large colour baseline will be used to investigate the age and metallicity distributions of the major structures of the bulge. Included in the survey footprint are 26 globular clusters imaged in all passbands. Over much of the bulge, we have Gaia DR2 matching astrometry to i ∼ 18, deep enough to reach the faint end of the red clump. This paper provides the background, scientific case, and description of the survey. We present an array of new reddening-corrected colour-magnitude diagrams that span the extent of Southern Galactic bulge. We argue that a population of massive stars in the blue loop evolutionary phase, proposed to lie in the bulge, are instead at ∼2 kpc from the Sun and likely red clump giants in the old disc. A bright red clump near (l, b) = (+ 8°, −4°) may be a feature in the foreground disc, or related to the long bar reported in earlier work. We also report the first map of the blue horizontal branch population spanning the Blanco DECam Bulge Survey field of regard, and our data do not confirm the reality of a number of proposed globular clusters in the bulge.
Gesehen am 22.01.2020